Pengembangan Formative Sebagai Media Evaluasi Maharah al-Istima’ dan al-Qira’ah Siswa Kelas X MAN Kota Batu Malang - Indah Rahmayanti; Sahrul Muhamad; Yadin La Udin; Durrotun Nashihah; Nur Qomari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
In the current digital era, technology plays a crucial role in supporting learning assessment methods. The use of technological devices in learning has become a major requirement in learning. In evaluating Arabic language lessons, a teacher is required to be able to present learning material questions in an innovative evaluation media to meet learning targets. This research aims to describe evaluation in Arabic language learning using formative media in evaluating listening and reading skills. The research employs a reseach and development ADDIE (Analysis, Design, Development, Implementation and Evaluation). Data collection involves literature review, documentation, and questionnaires distributed to 34 students. The results of this research found that formative evaluation media can support and make it easier for teachers to evaluate Arabic language learning, especially listening and reading skills. The media's advantages include diverse question types, audio-visual features, login functionality, scoring for each question item, and time limits for completion. With this conclusion, this media can be a solution for teachers in evaluating students' Arabic language skills. This research is still limited to evaluating listening and reading skills only, so suggestions for further research are to use this media to evaluate speaking and writing skills.